Breast radiology malpractice suits: Characteristics of frequency and outcomes‐ national and statewide distinctions. Issue 3 (15th November 2017) - Baker, Stephen R.; Pentakota, Sri Ram; Hubbi, Basil
Abstract: The purpose of this study was to determine the frequency and outcomes of breast malpractice suits among all enrollees in One Call Medical Inc.'s panel of interpreting radiologists nationally and to evaluate state‐by‐state variations. The 8401 radiologists enrolled had 4764 suits, of which 826 were related to breast disease. In New York and New Jersey, the ratio of breast suits to One Call Radiologists was 0.28 and 0.27, twice as much as in any other state. Breast suits in radiology have a wide variation in frequency across the country with New York and New Jersey far exceeding all others in relative frequency and number of radiologists with multiple breast suits.